تأثير مادة الالصول والتخزين تحت درجة حرارة المعمل على الإنضاج الصناعي لثمار الموز (Albayan Scientific Journal, 2023)
This experiment was conducted to test the efficiency of Alsol on the artificial ripening of green banana fruits, a local variety in Derna city. The treatments consisted of four concentrations of the substance (0, 500, 1000, 1500) ppm, and they were stored at room ambient temperature (16±2) and relative humidity  (55%)The experiment was designed on the basis of a complete random design (CRD), and the results obtained showed that treatment with the substance of Alsol has a significant effect on the coloration of the peel of the fruits, and the ratio of the peel to the pulp.  It has a significant effect on weight loss, which was increased with extending the storage period an result of increasin respiration rate and consumption of stored materials .The results also revealed that the substance of Alsol maintained the firmness of the fruits, and a slight increase in the percentage of total soluble solids, and this is one of the most important criteria for measuring the quality and degree of maturity of banana fruits